2019
DOI: 10.3390/ma12060889
|View full text |Cite|
|
Sign up to set email alerts
|

Unified Strength Model of Asphalt Mixture under Various Loading Modes

Abstract: Although the rutting resistance, fatigue cracking, and the resistance to water and frost are important for the asphalt pavement, the strength of asphalt mixture is also an important factor for the asphalt mixture design. The strength of asphalt mixture is directly associated with the overall performance of asphalt mixture. As a top layer material of asphalt pavement, the strength of asphalt mixture plays an indispensable role in the top structural bearing layer. In the present design system, the strength of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The suitability of UST for asphalt mixtures has been verified. However, it has mostly been carried out at specific temperatures (Suo et al, 2015;Yang et al, 2015;Xia et al, 2019). Considering the objectivity of temperature sensitivity of asphalt material, this section attempts to establish a unified strength model of asphalt mixture considering the temperature effect.…”
Section: Unified Strength Model Of Asphalt Mixture Considering Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…The suitability of UST for asphalt mixtures has been verified. However, it has mostly been carried out at specific temperatures (Suo et al, 2015;Yang et al, 2015;Xia et al, 2019). Considering the objectivity of temperature sensitivity of asphalt material, this section attempts to establish a unified strength model of asphalt mixture considering the temperature effect.…”
Section: Unified Strength Model Of Asphalt Mixture Considering Temperaturementioning
confidence: 99%
“…To establish an accurate theoretical model to describe the effect of intermediate principal stress on asphalt mixture strength. Some scholars explored and achieved important results under the unified strength model framework (Suo et al, 2011;Yu et al, 2011;Xia et al, 2019). Suo et al (2015) conducted orthogonal tests and confirmed the influence of the second principal stress, loading rate and temperature on the strength of asphalt mixture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fracture failure of asphalt concrete at low-temperature is complex, because it essentially depends on complex microstructures, temperature and fracturing modes, causing complex fracture patterns consisting of the main crack, crack branching and crack deflection [9,10]. Granting laboratory experiments have been widely adopted to investigate the fracture resistance [4,11] and cracking process [12,13] of asphalt concrete, which analyze the effect of temperatures [1,14,15,16], environmental factors [17,18] and fracturing modes [2,9,14,19], it is difficult to clearly reveal the effect of some important aggregate characteristics (e.g., morphological features and distribution), and require a high-cost and a lot of time for manufacturing samples. To contrast, the numerical simulation method has the advantage of characterizing these complex microstructures, saving research time and reducing experimental samples [20].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that asphalt mortar could be the closest subscale in terms of performance to that of asphalt mixtures, making it a vital scale to bridge the gap between asphalt binder and asphalt mixtures in multiscale performance analysis. A unified strength model, which can be used to overcome the design deviation caused by the randomness of the laboratory strength test and improve the accuracy degree, was described by Xia et al [28]. Different loading stresses were investigated to conclude the unified strength model, as well as to study the asphalt mixture moduli in the research presented by Fan et al [29].…”
mentioning
confidence: 99%